The dangers of smoking in bed : stories - Enriquez, Mariana (Hogarth, 2021)
"Mariana Enriquez has been critically lauded for her unconventional and sociopolitical stories of the macabre: populated by unruly teenagers, crooked witches, homeless ghosts, and hungry women, they walk the uneasy line between urban realism and horror. The stories in her next collection are as terrifying as they are socially conscious, and press into being the unspoken -- fetish, illness, the female body, the darkness of human history -- with unsettling urgency. A woman is sexually obsessed with the human heart; a lost, rotting baby crawls out of a backyard and into a bedroom; a pair of teenage girls can't let go of their idol; an entire neighborhood is cursed to death by a question of morality they fail to answer correctly. Written against the backdrop of contemporary Argentina, and with resounding tenderness towards those in pain, in fear, and in limbo, this new collection from one of Argentina's most exciting writers finds Enriquez at her most sophisticated, and most chilling"--